Teachers' Ecological Transformation in Artificial Intelligence Literacy: A Case Study on the Transition from an Anthropocentric to an Ecocentric Perspective - Ugras, Hilal; Ugras, Mustafa (Mdpi, 2026)
The aim of this study is to determine teachers' views on integrating sustainable artificial intelligence use into classroom teaching processes. The study was conducted using a qualitative research approach and adopted a case study design. The study group consisted of 38 teachers who were selected using maximum diversity sampling, who currently use AI, and who participated in a 4-week structured Sustainable AI Training Program. To ensure methodological triangulation, data were collected through semi-structured interviews, researcher diaries, and participant diaries and analyzed using inductive thematic content analysis. According to the analysis results, some findings reveal that teachers considered filtering AI tools through a pedagogical filter centered around the question Is it really necessary? rather than using them directly and intensively. Furthermore, digital minimalism was adopted in classroom practices, along with the use of a single, optimized prompt instead of trial-and-error queries, the practice of archiving and reusing generated content, and a shift toward low-tech alternatives. It was determined that teachers would adopt digital minimalism in classroom practices, aiming to serve as role models for sustainable use by bringing the hidden environmental costs of technology into the learning process and fostering eco-digital citizenship awareness among students. Consequently, AI integration has evolved from a technical decision into a pedagogical redesign process encompassing ethical and ecological dimensions.
Keywords: sustainable artificial intelligence; teacher education; green artificial intelligence; digital minimalism; eco-digital citizenship